The design and development of solar flat mirror (Solarux) system. (February 2016) - Toygar, Evren M.; Bayram, Tufan; Daş, Oğuzhan; Demir, Ali
Abstract: Low cost, two axis tracking solar dish with flat mirror system׳s (Solarux CSP) design and its advantages are described in this paper. System is based on the Concentrating Solar Power (CSP) technology. Heat energy and electricity are produced using oil and sunlight. In design stage, cost of production, constructability, automation, safety, cleaning and required energy that is required for the system have been taken into account. In this paper, it has been focusing on air-conditioning, heating, and producing electricity by using Solarux CSP. The aim of this invention is to use planar mirrors instead of parabolic mirrors in order to recuce cost and design a system that can be manufactured easily, can be constructed on every kind of terrain (rocky, plain etc.) and can be used by third world countries. For this purpose, for the development and design of solar flat system Solid Works 2012 has been used and the results are discussed and shown briefly.